Smart Learning Environment for Enhancing Digital Literacy of Thai Youth: A Case Study of Ethnic Minority Group - Temdee, Punnarumol (Wireless personal communications, 2021)
Digital literacy is needed for digital transformation. It is challenging to provide an appropriate digital literacy lesson for all people to satisfy their different goals. Therefore, the proper way of teaching and learning digital literacy requires personalized learning. Nowadays, the ethnic minority group can have equal access to a vast opportunity from the Internet through the smartphone. However, the Internet can also be harmful to them without proper protection. Therefore, it is necessary to promote digital literacy for them. This study proposes a smart learning environment for enhancing digital literacy of Thai youths from the ethnic minority group. The proposed smart environment modifies the objective distance, which is the distance between the satisfied and the current competency of each learner, for providing a personal learning path. There are 5 learning objects included. The experiment is conducted with 103 students who are the ethnic minority group in Chiang Rai province, Thailand. The comparison of post-test and pre-test reveals that the students can enhance their digital literacy after learning with the developed learning environment. Overall, the students agree on the provided personalized support. More specifically, they strongly agree that the provided content is suitable for their performances.